Hansen Solubility Parameter Analysis on Dispersion of Oleylamine-Capped Silver Nanoinks and their Sintered Film Morphology - Satoshi Saita; Shin-ichi Takeda; Hideya Kawasaki (Nanomaterials, 2022)
Optimizing stabilizers and solvents is crucial for obtaining highly dispersed nanoparticle inks. Generally, nonpolar (hydrophobic) ligand-stabilized nanoparticles show superior dispersibility in nonpolar solvents, whereas polar ligand (hydrophilic)-stabilized nanoparticles exhibit high dispersibility in polar solvents. However, these properties are too qualitative to select optimum stabilizers and solvents for stable nanoparticle inks, and researchers often rely on their experiences. This study presents a Hansen solubility parameter (HSP)-based analysis of the dispersibility of oleylamine-capped silver nanoparticle (OAm-Ag NP) inks for optimizing ink preparation. We determined the HSP sphere of the OAm-Ag NPs, defined as the center coordinate, and the interaction radius in 3D HSP space. The solvent’s HSP inside the HSP sphere causes high dispersibility of the OAm-Ag NPs in the solvent. In contrast, the HSPs outside the sphere resulted in low dispersibility in the solvent. Thus, we can quantitatively predict the dispersibility of the OAm-Ag NPs in a given solvent using the HSP approach. Moreover, the HSP sphere method can establish a correlation between the dispersibility of the particles in inks and the sintered film morphology, facilitating electronic application of the nanoparticle inks. The HSP method is also helpful for optimizing stabilizers and solvents for stable nanoparticle inks in printed electronics.